Scholarly Viewpoints, with Hans-Dieter Evers - Dieter, Hans (Penerbit Universiti Sains Malaysia (USM Press), 2015)
Hans-Dieter Evers is Professor Emeritus, Faculty of Sociology, University of Bielefeld, Germany; Senior Fellow, Center for Development Research, University of Bonn (on leave); Adjunct Professor of Sociology, Universitas Indonesia; and Visiting Professor, Universiti Kebangsaan Malaysia. He was formerly Lecturer of Sociology, Monash University; Associate Professor of Sociology and Director of Graduate Southeast Asia Studies at Yale University; Professor and Head, Department of Sociology, University of Singapore; and more recently Eminent Visiting Professor, Institute of Asian Studies, Universiti Brunei Darussalam. His current work is concentrated on the sociology of knowledge in Southeast Asia and on conceptions of maritime space in the South China Sea (Evers 2014). He has recently written or co-edited books on The Moral Economy of Trade (1974), Southeast Asian Urbanism (2002), The Straits of Malacca (2008), Governing and Managing Knowledge in Asia (2010) and Beyond the Knowledge Trap (2011)